2011
DOI: 10.1017/s0950268811000963
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence types of invasive Corynebacterium diphtheriae isolated in the Rio de Janeiro urban area, Brazil

Abstract: SUMMARYInvasive infections caused by Corynebacterium diphtheriae in vaccinated and non-vaccinated individuals have been reported increasingly. In this study we used multilocus sequence typing (MLST) to study genetic relationships between six invasive strains of this bacterium isolated solely in the urban area of Rio de Janeiro, Brazil, during a 10-year period. Of note, all the strains rendered negative results in PCR reactions for the tox gene, and four strains presented an atypical sucrose-fermenting ability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…However, ribotyping depends very much upon the use of a rigid standardized method, and without this, there might be difficulties in reproducibility. MLST overcomes some problems observed with ribotyping, previously considered the gold standard, by directly indexing nucleotide variation within several core metabolic genes, thereby providing high-resolution data appropriate for evolutionary and epidemiological investigations (17,18). The extended MLST scheme incorporating both C. diphtheriae and C. ulcerans provides a valuable tool for monitoring and characterizing circulating strains in the United Kingdom and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…However, ribotyping depends very much upon the use of a rigid standardized method, and without this, there might be difficulties in reproducibility. MLST overcomes some problems observed with ribotyping, previously considered the gold standard, by directly indexing nucleotide variation within several core metabolic genes, thereby providing high-resolution data appropriate for evolutionary and epidemiological investigations (17,18). The extended MLST scheme incorporating both C. diphtheriae and C. ulcerans provides a valuable tool for monitoring and characterizing circulating strains in the United Kingdom and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic numbers were assigned to each locus, creating a unique numerical profile, which was compared with C. diphtheriae sequences posted at http: //pubmlst.org/cdiphtheriae/. The profile obtained was 3, 2, 4, 1, 3, 3, 13, which was assigned sequence type 136 (ST136), a type unique among NML data and, to date, from published literature (3,11,18).…”
Section: Case Reportmentioning
confidence: 99%
“…These infections have a high mortality rate (up to 40%), which can be explained by the presence of comorbidity (cardiac valvulopathy) (7) and predisposing conditions (intravenous drug use, skin lesions, and socioeconomic disadvantage) (4,10). Several studies using ribotyping have suggested the invasive isolates to be clonal (4, 6, 10) whereas others have found multiple types of C. diphtheriae bacteria (11).…”
mentioning
confidence: 99%
“…A single isolate collected in 1991 was ST39. Notably, ST39 was also recovered in 1999 in the United States (in California and Maine), where it caused at least two other bacteremias, one case of arthritis and one upper respiratory tract infection (11).…”
mentioning
confidence: 99%